Hospital resuscitation from ventricular fibrillation in Brighton. - Mackintosh, A F (1979)
The overall results over three and a half years of the treatment of ventricular fibrillation secondary to ischaemic heart disease in the Royal Sussex County Hospital were reviewed. Records of all patients who were brought to hospital by resuscitation ambulances or who were admitted to the coronary care unit from any source were analysed. Eighty-seven of the 174 patients (50%) who developed ventricular fibrillation were discharged. The survivors included 13 out of 61 patients (21%) in whom fibrillation was secondary to cardiogenic shock or severe left ventricular failure. The presence of resuscitation equipment and nursing staff trained to use it in the general wards and emergency areas ensured a uniformly high success rate throughout the hospital, similar to that achieved in the coronary care unit. Prompt defibrillation in the general wards and the accident and emergency department may improve overall survival.